Enhanced dielectric response in Ca(Fe, Nb)O3-TiO2 composite ceramics. Issue 14 (1st October 2018) - Zeng, Yi; Bokov, Alexei A.; Wang, Dawei; Xiang, Feng; Wang, Hong
Abstract: We studied temperature and frequency dependences of dielectric properties of (1- x )Ca(Fe1/2 Nb1/2 )O3 - x TiO2 (CFNT) composite ceramics in the ranges of 90–700 K and 10 2 10 6 Hz, respectively. Then we detected relaxation in the permittivity formalism. Most interestingly, a large and temperature-independent permittivity of 10 5 could be obtained in the hetero-phase compound with x = 0.5 by interface engineering. The results were interpreted in terms of Maxwell-Wagner relaxation, which accounts for the fact that the grains and grain boundaries have very different conductivity.